2000
DOI: 10.1002/(sici)1098-237x(200003)84:2<212::aid-sce5>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

The use of secondary science classroom teaching assistant experiences to recruit academically talented science majors into teaching

Abstract: The study was conducted to determine whether a classroom teaching assistant project could help recruit academically talented undergraduate science majors into teacher preparation. Academically talented science majors were identified by science course grade‐point averages. The majors spent 10 hours each week for approximately 10 weeks assisting carefully selected secondary science teachers in their classroom teaching activities. Science teachers were selected for the project based on their reputations as creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Pre-service and in-service science teachers most frequently cite their affinity for science (Bull et al, 1994;Dawson, 2007;Dominguez et al, 2015;Eick, 2002;Espinet et al, 1992;Kilinç & Seymen, 2014) and desire to make a positive social impact (Bull et al, 1994;Dawson, 2007;Dominguez et al, 2015;Eick, 2002;Kilinç & Seymen, 2014) as the reasons why they entered the field of science education. Additional motivations for entering science teaching include a desire to work with youth (Bull et al, 1994;Dawson, 2007;Espinet et al, 1992;Kilinç & Seymen, 2014, Westerlund et al, 2011, positive prior teaching experience (Dawson, 2007;Kilinç & Seymen, 2014;Luft et al, 2005;Wang, 2004), positive impact by a former teacher (Dawson, 2007;Tomanek & Cummings, 2000), valuing the teaching profession (Dawson, 2007;Dominguez et al, 2015;Espinet et al, 1992;Kilinç & Seymen, 2014), and an opportunity to engage with science (Eick, 2002;Tomanek & Cummings, 2000). Although not cited as a motivating factor in studies of U.S. pre-and in-service science teachers, studies of science teacher recruitment conducted internationally have also identified job conditions (such as salary, demand, and workload) as having a positive impact on students' decision to pursue science teaching (Dawson, 2007;Dominguez et al, 2015;Kilinç & Seymen, 2014;Wang, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Pre-service and in-service science teachers most frequently cite their affinity for science (Bull et al, 1994;Dawson, 2007;Dominguez et al, 2015;Eick, 2002;Espinet et al, 1992;Kilinç & Seymen, 2014) and desire to make a positive social impact (Bull et al, 1994;Dawson, 2007;Dominguez et al, 2015;Eick, 2002;Kilinç & Seymen, 2014) as the reasons why they entered the field of science education. Additional motivations for entering science teaching include a desire to work with youth (Bull et al, 1994;Dawson, 2007;Espinet et al, 1992;Kilinç & Seymen, 2014, Westerlund et al, 2011, positive prior teaching experience (Dawson, 2007;Kilinç & Seymen, 2014;Luft et al, 2005;Wang, 2004), positive impact by a former teacher (Dawson, 2007;Tomanek & Cummings, 2000), valuing the teaching profession (Dawson, 2007;Dominguez et al, 2015;Espinet et al, 1992;Kilinç & Seymen, 2014), and an opportunity to engage with science (Eick, 2002;Tomanek & Cummings, 2000). Although not cited as a motivating factor in studies of U.S. pre-and in-service science teachers, studies of science teacher recruitment conducted internationally have also identified job conditions (such as salary, demand, and workload) as having a positive impact on students' decision to pursue science teaching (Dawson, 2007;Dominguez et al, 2015;Kilinç & Seymen, 2014;Wang, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A multitude of recruitment strategies, seeking either to identify science majors with nascent interest in science teaching or to inspire such interest in science majors who would never otherwise consider science teaching, have been recommended in the literature, although the efficacy of only a few have been evaluated. The most widely supported recruitment strategy is providing science majors with science teaching experience (Borgerding, 2015;Saxman et al, 2010;Schuster, 2013;Tomanek & Cummings, 2000;Worsham et al, 2013). Financial incentives (in the form of stipends, scholarships, and tuition remission) are another widely utilized recruitment strategy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies examining the teaching field experiences of STEM undergraduates revealed positive benefits, including how these experiences shape attitudes about science and math teaching careers and the teaching profession generally (Bischoff, French, & Schaumloffel, 2014;Borgerding, 2015;Fletcher & Luft, 2011;Tomanek, 1996;Tomanek & Cummings, 2000;van den Kieboom, McNew-Birren, Eckman, & Silver-Thorn, 2013). These studies featured small numbers of participants, ranging from a single-case narrative to 22 participants.…”
Section: Stem Undergraduates' Field Experiencesmentioning
confidence: 99%